2015
DOI: 10.1002/pros.23019
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and risk of prostate cancer: Results from the Southern Community Cohort Study

Abstract: Background Epidemiologic studies suggest that statin use may be inversely associated with risk of prostate cancer, but prior studies have focused predominantly on non-Hispanic white populations. Methods We evaluated the association between statin use and prostate cancer risk in the Southern Community Cohort Study (SCCS). Study participants were 32,091 men aged 40-79 at baseline, 67% of whom were non-Hispanic black. Between study enrollment (2002-2009) and December 31, 2010, 570 prostate cancer cases were dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
3
17
0
Order By: Relevance
“…We observed a similar magnitude of association between statin use and prostate cancer aggressiveness in both CAs and AAs; findings were supported by a prior study, which found that associations between statin use and risk of high-grade prostate cancer did not vary by race (16). In contrast to prior cohort and case-control analyses of statin use and prostate cancer risk using prostate cancer-free men as the referent group (5, 8, 16), the case-only design of this study examined the impact of statin use on disease aggressiveness among men diagnosed with prostate cancer.…”
Section: Discussionsupporting
confidence: 89%
“…We observed a similar magnitude of association between statin use and prostate cancer aggressiveness in both CAs and AAs; findings were supported by a prior study, which found that associations between statin use and risk of high-grade prostate cancer did not vary by race (16). In contrast to prior cohort and case-control analyses of statin use and prostate cancer risk using prostate cancer-free men as the referent group (5, 8, 16), the case-only design of this study examined the impact of statin use on disease aggressiveness among men diagnosed with prostate cancer.…”
Section: Discussionsupporting
confidence: 89%
“…A retrospective cohort study in Israel of 37,645 men taking statins found a 74% reduced risk of total prostate cancer in long-term statin users, defined as >5 years of statin use, in comparison with nonusers 74 . Other studies found weaker but still inverse associations between statin use and total prostate cancer risk 75,76 , including a population-based study in Washington, USA, that found that statin users had a nonsignificant 12% lower prostate cancer risk 17 .…”
Section: Epidemiological Evidencementioning
confidence: 93%
“…Six large, prospective studies all found that statin users had a reduced risk of advanced prostate cancer without any reduction, or with an attenuated reduction, in total prostate cancer risk 8,9,11,76,80,82 . In all six studies, bias was minimized by controlling for potential confounding variables, for example, concomitant diseases, such as diabetes, use of antidiabetic drugs or other treatments and cardiovascular risk factors that are associated with prostate cancer risk, such as age, race and body mass index.…”
Section: Epidemiological Evidencementioning
confidence: 99%
See 2 more Smart Citations